Modest Target For Frences Will Take A Stab At Creating Upsets - The Star, Ng Wei Loon (2008)
The Selangor Amateur Fencing Association (SAFA) have set a modest target for the Malaysia Games (Sukma) to be held in Terengganu from tomorrow to June 9.